2016
DOI: 10.1056/nejmoa1603017
|View full text |Cite
|
Sign up to set email alerts
|

Initiation Strategies for Renal-Replacement Therapy in the Intensive Care Unit

Abstract: In a trial involving critically ill patients with severe acute kidney injury, we found no significant difference with regard to mortality between an early and a delayed strategy for the initiation of renal-replacement therapy. A delayed strategy averted the need for renal-replacement therapy in an appreciable number of patients. (Funded by the French Ministry of Health; ClinicalTrials.gov number, NCT01932190.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
828
3
33

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 905 publications
(894 citation statements)
references
References 40 publications
30
828
3
33
Order By: Relevance
“…Three RCTs258, 259, 260 were used to perform the new meta‐analysis. In the results, the impact of early‐stage initiation of blood apheresis on 28‐day or 30‐day mortality was a risk ratio of 0.83 (95% confidence interval [CI]: 0.64–1.09), and a risk ratio of 0.51 for the rate of dialysis dependence on day 60 (95% CI: 0.25–1.06).…”
Section: Cq12: Acute Kidney Injury/blood Apheresismentioning
confidence: 99%
“…Three RCTs258, 259, 260 were used to perform the new meta‐analysis. In the results, the impact of early‐stage initiation of blood apheresis on 28‐day or 30‐day mortality was a risk ratio of 0.83 (95% confidence interval [CI]: 0.64–1.09), and a risk ratio of 0.51 for the rate of dialysis dependence on day 60 (95% CI: 0.25–1.06).…”
Section: Cq12: Acute Kidney Injury/blood Apheresismentioning
confidence: 99%
“…Die deutsche ELAIN-Studie ("early versus late initiation of renal replacement therapy in critically ill patients"; [36]) und die französische AKI-KI-Studie ("the artificial kidney initiation in kidney injury"; [6]) untersuchten diese Fragestellung. Bei ELAIN handelt es sich um eine monozentrische Studie anhauptsächlich herzchirurgischen postoperativen Patienten (n = 231).…”
Section: Beginn Der Nierenersatztherapieunclassified
“…These trials immediately revived the heated debate on when to start renal replacement therapy. In the study of Gaudry et al (9) patients did not show a survival benefit at day 60, whereas Zarbock et al (10) demonstrated a significantly reduced 90-day all-cause mortality with early initiation of renal replacement therapy. How is it that two studies addressing exactly the same problem reach such opposing conclusions?…”
mentioning
confidence: 95%